Dominating Concepts of Russian Federation Propaganda Against Ukraine (Content and Collocation Analyses of Russia Today) - Karpchuk, Nataliia; Yuskiv, Bohdan (Politologija, 2021)
The Russian Federation has been carrying out long-term and successful disinformation and propaganda activities against Ukraine. Due to its powerful, state-supported media structures, it is able to impose its vision of reality on its respective audiences. The purpose of this article is to determine the lexemes and topics of the “landscape” of analytical reports produced by Russia Today (RT) in 2018–2020. Lexemes and topics lay the groundwork for the RT propaganda discourse aimed at interfering and disbalancing Ukraine’s media space. This paper, based on quantitative and qualitative analysis, focuses on (1) the vocabulary structure of analytical materials, which may indicate Russian priorities, and (2) the thematic content (hidden topics) of RT messages. The RT analytical reports titles and relevant metadata were analyzed. The body of data was subdivided into periods of presidencies of P. Poroshenko and V. Zelensky. The authors argue that personalities do not play a significant role in the Kremlin’s attitude toward Ukraine; only the Ukraine-Russia opposition is decisive, in which the RF assigns Ukraine the only acceptable role as Russia’s “puppet.”